Viktor Emil Frankl and the Logoterapy: history, concept and applications - Clemente, Ednilson; Krüger, Rolf Roberto (Vox Scripturae - Revista Teológica Internacional, 2016)
The present research begins with a brief approach to data from Viktor Frankl’s biography, especially his period in the Auschwitz concentration camp and the experiences that inspired him to develop his understanding of Logotherapy. In the following part of this research, the foundations of Logotherapy are worked out, especially the concepts of will of meaning, existential frustration and neurosis, noodynamics, existential emptiness, meaning of life, sense of love, sense of suffering, supra sense of life and transience of life. In the next part are discussed the dimensions of the Logotherapy as a technique, its relationship with the pastoral clinic and its applicability to the treatment of chemical dependents.